Assessment of patients satisfaction with mobile medical clinics in the two districts of north Bengal, India - Mahapatra, Biswajit; Moinudeen, Syed Abdul Khader; Bhattacharya, Paramita; Mukherjee, Nirmalya; John, Denny; Jayanna, Krishnamurthy (International Journal Of Community Medicine And Public Health, 2023)
Background: Patient satisfaction is an important indicator to measure the quality of healthcare services and plays a crucial role in enhancing the quality of health service delivery. The aim of the study was to assess the patient’s satisfaction level with the quality of health care delivered at the mobile medical clinics (MMC) in two districts of north Bengal, India. Methods: A cross-sectional survey was done using a purposive sampling method, and total of 294 samples were recruited. A questionnaire (PSQ-18) was used to assess the patient satisfaction level. Chi-square tests were used for categorical variables. F-test and t-test were used for mean differences between the variables. Linear regression analysis was done to examine the linear effect of social factors on patient satisfaction. Results: The present study shows that overall satisfaction was 74.04%, with a mean value of 3.702. In the Jalpaiguri district, 27.5% of patients are highly satisfied, whereas 17.0% are in Alipurduar. Alipurduar district has a higher low satisfaction rating (39.7%) than Jalpaiguri district (19.7%), and a district-wise significant association was found (p<0.001). Overall satisfaction level effects by occupation (p<0.001), population and socio economic status (p<0.05). Conclusions: Policymakers may consider that MMCs could be an effective strategy to improve primary health care in remote, underserved areas where there are no public health care facilities.